Assessment of the position and level of mental nerve for placement of implants using cone-beam computed tomography & panoramic radiograph in the Saudi population - Nabeeh A. AlQahtani (Elsevier, 2022)
Background and objective: In surgical dentistry, shape, location, position, and extent of the anterior loop of mental foramen plays a deliberately imperative landmark during an osteotomy procedure. To evade any neurological disturbance during implant surgery radiological assessment is compulsory. Therefore, the aim of the study was to assess the position and level of mental nerve for placement of implants using Cone-beam computed tomography & Panoramic radiography in the Saudi population. Materials and methods: A total of 150 CBCT and Panoramic radiographs were taken from the patients who visited the Department of Oral Medicine and Radiology. The data collection was done by using the same radiographic pieces of equipment for both CBCT and Panoramic radiographs. CBCT images taken from Kodak 9000 3D, Carestream Health, Inc., New York, USA, and Panoramic Radiographs taken from Panoramic Planmeca ProMax, Helsinki, Finland (Vujanovic-Eskenazi et al., 2015). The Chi-square test student test was used for statistical analysis. Results: The most frequent shape and location of mental foramen in both CBCT and Panoramic radiographs were oval and in between the first and second premolar, both in CBCT & PR views. The visibility of mental loop on CBCT & PR view showed that; visibility of mental loop in CBCT was higher with 42(56%) as compared with PR view 26(34.66%) with statistically significant p-value 0.014. The mean length of the mental loop on CBCT was statistically significant (p = 0.001). But the mean distance from the lower point of the mental foramen to the lower border of the mandible was not statistically significant. Conclusion: Based on the results of the present study; the visibility of the mental loop and its extension is more in CBCT as compared with PR views. Therefore, we recommended CBCT, during of implant surgery.